Evaluasi Kinerja Pelayanan Publik Di Kantor Kelurahan Ngronggo Kota Kediri - Muhamad Ansori (Universitas 17 Agustus 1945 Semarang, 2025)
Public service is a fundamental aspect of government to fulfil the needs of the community in a fair, efficient, and quality manner. This study aims to evaluate the performance of public services in Kelurahan Ngronggo, Kediri City, based on relevant service indicators. The research used a descriptive qualitative approach with primary data from interviews and observations, and secondary data from official reports. The results showed that the quality of service in 2023 was in the good category with an IKM value of 86.54, but decreased compared to 2022 which reached 91.31 (very good). This decline was caused by limited technological infrastructure, lack of employee training, uneven distribution of tasks, and complicated administrative procedures. To address these issues, the recommended strategic measures include technological updates, regular training, digitisation of the service system, increased cooperation between employees, and simplification of administrative procedures. With the implementation of these strategies, it is expected that the quality of public services in Kelurahan Ngronggo can improve, fulfil community expectations, and build public trust in the government.